Determining the Shortwave Radiative Flux From Earth Polychromatic Imaging Camera. Issue 20 (29th October 2018) - Su, Wenying; Liang, Lusheng; Doelling, David R.; Minnis, Patrick; Duda, David P.; Khlopenkov, Konstantin; Thieman, Mandana M.; Loeb, Norman G.; Kato, Seiji; Valero, Francisco P. J.; Wang, Hailan; Rose, Fred G.
Abstract: The Earth Polychromatic Imaging Camera (EPIC) onboard Deep Space Climate Observatory provides 10 narrowband spectral images of the sunlit side of the Earth. The blue (443 nm), green (551 nm), and red (680 nm) channels are used to derive EPIC broadband radiances based upon narrowband‐to‐broadband regressions developed using collocated MODIS equivalent channels and Clouds and the Earth's Radiant Energy System (CERES) broadband measurements. The pixel‐level EPIC broadband radiances are averaged to provide global daytime means at all applicable EPIC times. They are converted to global daytime mean shortwave (SW) fluxes by accounting for the anisotropy characteristics using a cloud property composite based on lower Earth orbiting satellite imager retrievals and the CERES angular distribution models (ADMs). Global daytime mean SW fluxes show strong diurnal variations with daily maximum‐minimum differences as great as 20 W/m 2 depending on the conditions of the sunlit portion of the Earth. The EPIC SW fluxes are compared against the CERES SYN1deg hourly SW fluxes. The global monthly mean differences (EPIC‐SYN) between them range from 0.1 W/m 2 in July to −4.1 W/m 2 in January, and the RMS errors range from 3.2 to 5.2 W/m 2 . Daily mean EPIC and SYN fluxes calculated using concurrent hours agree with each other to within 2% and both show a strong annual cycle. The SW flux agreement is within the calibration and algorithm uncertainties, which indicates that the method developed to calculate the global anisotropic factors from the CERES ADMs is robust and that the CERES ADMs accurately account for the Earth's anisotropy in the near‐backscatter direction. Plain Language Summary: Measurements from Earth Polychromatic Imaging Camera onboard Deep Space Climate Observatory were used to derive the global daytime mean shortwave fluxes. They agree with those derived from the Clouds and the Earth's Radiant Energy System to within 2%. Key Points: Global daytime mean radiances from EPIC are converted to SW fluxes by accounting for the anisotropy using CERES angular distribution models The global monthly mean daytime SW fluxes from EPIC agree with those from CERES to within 2% The CERES angular distribution models accurately account for the Earth's anisotropy in the near‐backscatter direction